Reduced Adipose Tissue Macrophage Content Is Associated With Improved Insulin Sensitivity in Thiazolidinedione-Treated Diabetic Humans - Koppaka, Sudha (American Diabetes Association, 2013)
Obesity is associated with increased adipose tissue macrophage (ATM) infiltration, and rodent studies suggest that inflammatory factors produced by ATMs contribute to insulin resistance and type 2 diabetes. However, a relationship between ATM content and insulin resistance has not been clearly established in humans. Since thiazolidinediones attenuate adipose tissue inflammation and improve insulin sensitivity, we examined the temporal relationship of the effects of pioglitazone on these two parameters. The effect of 10 and 21 days of pioglitazone treatment on insulin sensitivity in 26 diabetic subjects was assessed by hyperinsulinemic-euglycemic clamp studies. Because chemoattractant factors, cytokines, and immune cells have been implicated in regulating the recruitment of ATMs, we studied their temporal relationship to changes in ATM content. Improved hepatic and peripheral insulin sensitivity was seen after 21 days of pioglitazone. We found early reductions in macrophage chemoattractant factors after only 10 days of pioglitazone, followed by a 69% reduction in ATM content at 21 days and reduced ATM activation at both time points. Although markers for dendritic cells and neutrophils were reduced at both time points, there were no significant changes in regulatory T cells. These results are consistent with an association between adipose macrophage content and systemic insulin resistance in humans.